Applied markovian approach for determining optimal process means in single stage SME production system - Hasan Basari, Abd Samad; Hussin, Burairah; Asmai, Siti Azirah; Ibrahim, Nuzulha Khilwani; Shibghatullah, Abdul Samad (IJACS 2011, 2011)
The determination of optimum process mean has become one of the focused research area in order to improve product quality. Depending on the value of quality characteristic of juice filling in the bottle, an item can be reworked, accepted or accepted with penalty cost by the system which is successfully transform to the finishing product by using the Markovian model. By assuming the quality characteristic is normally distributed, the probability of rework, accept and accept with penalty cost is obtained by the Markov model and next the optimum of process mean is determined which maximizes the expected profit per item. In this paper, we present the analysis of selecting the process mean in the filling process. By varying the rework and accept with penalty cost, the analysis shown the sensitivity of the Markov approach to determine the process mean.